PERSİAN VERBS: STRUCTURE & TENSE - Rubaba Teymurova; Salman Aliyev (Theoretical Hypotheses and Empirical Results, 2025)
This article delves into the intricate yet systematic nature of language and its role as a fundamental medium of human communication. It highlights how grammar, as a branch of linguistics, underpins our ability to exchange ideas and regulate thought by studying the phonetic, morphological, syntactic, and semantic aspects of language. The discussion focuses particularly on the verb—a central element in both spoken and written discourse—by reviewing its classification within Persian grammar. Various scholarly perspectives are examined, revealing ongoing debates on how verbs should be divided according to structure, including distinctions between simple, prefixed, compound, and group verbs, as well as differing views on the present tense. The article also provides an in-depth analysis of the formation of the absolute past (mazi‑ye motlagh) in Persian, detailing its derivation from the verb stem, conjugation patterns, and the specialized methods used for negation, which even extend to unique forms found in classical poetry.